1986
DOI: 10.1007/bf01913894
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolytic decomposition of some even chain length copper (II) carboxylates

Abstract: The products of the pyrolytic decomposition of some even chain-length copper (II) carboxylates from decanoate to octadecanoate inclusive have been identified, using a flow system, to be copper, carbon dioxide, a carboxylic acid and an odd chain-mength alkene. These products are similar to those reported for the decomposition of mercury(lI) carboxylates. The unexpectedly low (less than unity) CO2/soa p ratio was attributed to the reduction of the CO 2 to carbon monoxide. The carboxylic acid was characterised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…No alkene was found, unlike for the decomposition of even chain Cu/Hg carboxylate [24,25], suggesting that the chain length may also play a role in the decomposition pathway or that the decomposition mechanism is a result of the general catalytic activity of copper, resulting in the oxidation of ethylene to acetaldehyde [59].…”
Section: Discussionmentioning
confidence: 99%
“…No alkene was found, unlike for the decomposition of even chain Cu/Hg carboxylate [24,25], suggesting that the chain length may also play a role in the decomposition pathway or that the decomposition mechanism is a result of the general catalytic activity of copper, resulting in the oxidation of ethylene to acetaldehyde [59].…”
Section: Discussionmentioning
confidence: 99%
“…Though the thermal degradation of copper(II) carboxylates is to this day largely under investigated. Studies by Van My and coworkers [174] showed that the thermal degradation of short chain copper(II) carboxylates produced metallic copper under inert atmosphere whilst the oxide was produced in air [39,40] along with the parent alkanoic acid and or the a-olefin in some cases [175]. However, no comprehensive mechanism or kinetic models were proposed for their degradation behaviors.…”
Section: Divalent Carboxylatesmentioning
confidence: 99%
“…Consequently, the TG curves of 3 and 4 appear to exhibit four steps whereas 2 shows five steps of thermal degradation at a glance. Magnitude of final residue from all the three complexes is higher than that calculated for one mole of metal [28,[29][30][31] probably due to carbonaceous matter alongwith reduced metal. Further, it is worth to be mentioned that rerecorded TG curve of the heterobimetallic complex 4 on simultaneous TGA/DTA-MS device is superimposable on its original TG curve (Fig.…”
Section: Thermal Behaviour Of 2 Under Helium Atmospherementioning
confidence: 97%